World Workshop on Oral Medicine VII: Functional pathways involving differentially expressed lncRNAs in oral squamous cell carcinoma. (29th May 2019) - Pentenero, Monica; Bowers, Leah; Jayasinghe, Ruwan; Cheong, Sok Ching; Farah, Camile S.; Kerr, Alexander Ross; Alevizos, Ilias
Abstract: Long non‐coding RNAs (lncRNA) modulate gene expression at the epigenetic, transcriptional and post‐transcriptional levels and are involved in tumorigenesis. They can form complex secondary and tertiary structures and have been shown to act as precursors, enhancers, reservoirs and decoys in the complex endogenous RNA network. They were first reported in relation to oral squamous cell carcinoma (OSCC) in 2013. Here, we summarise the functional roles and pathways of the most commonly studied lncRNAs in OSCC. Existing research demonstrates the involvement of lncRNA within pivotal pathways leading to the development and spread of OSCC, including interactions with key cancer‐associated microRNAs such as miR‐21. The number of studies on lncRNA and OSCC remains limited in this new field. As evidence grows, the tissue‐specific expression patterns of lncRNAs should further advance our understanding of the altered regulatory networks in OSCC and possibly reveal new biomarkers and therapeutic targets.